Adenosine Kinase Inhibition Prevents Severe Acute Pancreatitis via Suppressing Inflammation and Acinar Cell Necroptosis - Sun, Shukun; Han, Yu; Zhang, Chuanxin; Liu, Han; Wang, Bailu; Cao, Shengchuan; Yuan, Qiuhuan; Wei, Shujian; Chen, Yuguo (Frontiers in Cell and Developmental Biology, 2022)
Background: Inflammatory disorder and acinar cell death contribute to the initiation and progression of severe acute pancreatitis (SAP). Adenosine kinase has potential effects on both inflammation and cell death. However, the role of ADK in SAP remains to be explored. Methods: To establish an experimental SAP model, male C57BL/6 mice were intraperitoneally injected with cerulein (50 μg/kg, 7 doses at hourly intervals) and LPS (10 mg/kg, at the last cerulein injection). For ADK inhibition, ABT702 (1.5 mg/kg) was intraperitoneally injected 1 hour before the exposure to the cerulein treatment. The pancreas and serum were collected and analyzed to determine the severity of the pancreatic injury and to explore the potential pathophysiological mechanisms. In vitro, pancreatic acinar cells (AR42J) were used to explore the effects of ADK inhibition on the cerulein–induced inflammation and necroptotic cell death. Results: ADK inhibition notably attenuated the severity of SAP indicated by the decreased serum amylase and lipase levels and the fewer pancreatic histopathological alterations. MOMA-2 and CD11b staining confirmed that ADK inhibition prevented the infiltration of neutrophils and macrophages. The phosphorylation of nuclear factor-κB (NF-κB) was also reduced by ADK inhibition. ADK inhibition markedly limited the area of the necrotic pancreas and prevented the activation of the necroptotic signal pathway. Endoplasmic reticulum (ER) stress was activated in the pancreas from the SAP model and the cerulein–treated AR42J cells whereas ADK inhibition reversed the activation of ER stress both in vivo and in vitro. Moreover, the alleviating effects of ADK inhibition on ER stress, inflammation, and cell necroptosis were eliminated by the adenosine A2A receptor antagonist. Conclusion: ADK inhibition reduced inflammation and necroptotic acinar cell death in SAP via the adenosine A2A receptor/ER stress pathway, suggesting that ADK might be a potential therapeutical target for SAP.